2011
DOI: 10.3382/ps.2010-01035
|View full text |Cite
|
Sign up to set email alerts
|

Dietary protein effects on hen performance and nitrogen excretion

Abstract: Because dietary nitrogen intake affects nitrogen content in manure, diet management has been recognized as a means to reduce ammonia emissions from poultry operations. The objectives of the present research were 1) to determine the extent to which the CP content of laying diets can be reduced, based on performance criteria, and 2) to determine how ash:nitrogen ratios of manure, eggs, and hens are affected by dietary protein changes. Egg-type hens were fed equal daily amounts of essential amino acids in diets t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
27
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 15 publications
7
27
1
1
Order By: Relevance
“…These results are in agreement with those of Latshaw and Zhao (2011) who found that changes in the level of protein in diet did not affect the rate of egg production and egg mass. Similar results were also observed by Rao et al (2011) andLi et al (2012).…”
Section: P-valuesupporting
confidence: 83%
“…These results are in agreement with those of Latshaw and Zhao (2011) who found that changes in the level of protein in diet did not affect the rate of egg production and egg mass. Similar results were also observed by Rao et al (2011) andLi et al (2012).…”
Section: P-valuesupporting
confidence: 83%
“…Therefore, although microbial fermentation of proteins which escaped from the host's digestive tract seems positive and beneficial, it contributes new problems. Latshaw and Zhao (2011) suggested that, in order to defeat these problems, protein content in a feed diet should be reduced. Other data implied usage of pro-and prebiotics, which acidify the intestinal content, decrease the protein fermentation inside the GIT and lower the activity of enzymes responsible for formation of toxins (De Preter et al 2006).…”
Section: Influence Of Gut Microbiota On Its Hostmentioning
confidence: 99%
“…Podobnie dzieje się w przypadkach diety bogatej w tłuszcze zwierzęce. Liczba wspomnianych drobnoustrojów nie wzrasta natomiast, kiedy do paszy dodawany jest olej sojowy (44,58,67).…”
unclassified